2012
DOI: 10.1029/2012ja017753
|View full text |Cite
|
Sign up to set email alerts
|

Signature of the coronal hole near the north crest equatorial anomaly over Egypt during the strong geomagnetic storm 5 April 2010

Abstract: International audienceIn this paper we study the ionospheric-magnetic disturbance during a strong magnetic storm on 5 April 2010 associated to a coronal hole. The Earth was under the influence of a high speed solar wind stream during four days, and IMF was southward during a very long period. The variation of the disturbed magnetic observations and GPS-TEC are compared with the variation of quiet days during the same month in order to obtain the characteristics of GPS-TEC and magnetic disturbances due to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…These decreases were majorly observed during the post-noon as well as the night time period. This is consistent with Danilov and Lastovicka (2001), Yizengaw et al (2005) Olawepo and Adeniyi (2012) and Shimeis et al (2012). It can be attributed to the long duration of the southward orientation of Bz experience during this storm event.…”
Section: August 3-4 2010 Moderate Stormsupporting
confidence: 92%
See 3 more Smart Citations
“…These decreases were majorly observed during the post-noon as well as the night time period. This is consistent with Danilov and Lastovicka (2001), Yizengaw et al (2005) Olawepo and Adeniyi (2012) and Shimeis et al (2012). It can be attributed to the long duration of the southward orientation of Bz experience during this storm event.…”
Section: August 3-4 2010 Moderate Stormsupporting
confidence: 92%
“…2a). The solar wind speed increased from around 500-700 km/s at the time of the SSC, reaching a maximum speed of 814 km/s at 1400 UT on 5 April, this speed was reported to have been flowing from a solar coronal hole (Shimeis et al, 2012), shown in Fig. 2c.…”
Section: Scalementioning
confidence: 93%
See 2 more Smart Citations
“…This measurement is named vertical TEC (vTEC). To convert sTEC to vTEC, we used the following equation: We also used the magnetic indices Dst, AU and AL with a time resolution of 1min (http://isgi.latmos.ipsl.fr/lesdonne.htm /), see Shimeis et al (2012) for more details.…”
Section: Data Set and Data Processingmentioning
confidence: 99%